Free vibrations of functionally graded material cylindrical shell closed with two spherical caps. (3rd April 2022) - Bagheri, H.; Kiani, Y.; Bagheri, N.; Eslami, M. R.
ABSTRACT: Free vibration response of a cylindrical shell closed with two hemispherical caps at the ends (hermit capsule) is analysed in this research. It is assumed that the system of joined shell is made from functionally graded materials (FGM). Properties of the shells are assumed to be graded through the thickness. Cylindrical and hemispherical shells are unified in thickness. To capture the effects of through-the-thickness shear deformations and rotary inertias, first order theory of shells is used. Donnell type of kinematic assumptions are adopted to establish the general equations of motion and the associated boundary and continuity conditions with the aid of Hamilton's principle. The resulting system of equations are discretised using the semi-analytical generalised differential quadrature (GDQ) method. After proving the efficiency and validity of the present method for the case of isotropic homogeneous joined shells, some parametric studies are carried out for the system of combined FGM hermetic capsule.